Drivers of Competitive Advantage and Marketing Performance In Bag MSMEs - Leny Muniroh; Nora Azmia; Lelih Amaliatushalihah; Erlangga Ferdiansyah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The marketing performance of bag MSMEs in Bogor is a complex phenomenon and still faces challenges, such as limited resources, lack of digital technology utilization, and lack of effective partnerships. This makes it difficult for bag MSMEs to improve their competitive advantage and marketing performance. This study aims to analyze and empirically prove the influence of internal resources , digital marketing , and partnership strategies on competitive advantage and their implications for marketing performance in bag Micro, Small, and Medium Enterprises (MSMEs) in Bogor. The research approach uses a quantitative method with causality analysis. The population consists of 112 bag MSMEs, with a sample of 88 bag MSMEs. The instrument is a questionnaire with 47 valid and reliable indicators, analyzed using Structural Equation Modeling (SEM) with SmartPLS version 4.1.0.5. The results of the study indicate that internal resources and digital marketing significantly influence competitive advantage. Digital marketing is the dominant factor, emphasizing the importance of digital transformation in building competitiveness. Furthermore, marketing performance is significantly influenced by internal resources , digital marketing , and competitive advantage. However, partnership strategies do not have a significant effect, either directly or indirectly, on competitive advantage and marketing performance. The results of this study are expected to contribute to the marketing literature and provide practical implications for MSMEs in developing effective marketing strategies to improve marketing performance and competitive advantage.   Keywords: MSMEs, internal resources, digital marketing, partnership strategy, marketing performance